1989
DOI: 10.1002/1097-0142(19891215)64:12<2448::aid-cncr2820641209>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate, vinblastine, doxorubicin, and cisplatin for advanced transitional cell carcinoma of the urothelium. Efficacy and patterns of response and relapse

Abstract: Of 133 patients with advanced urothelial tract cancer given methotrexate (MTX), vinblastine (VBL), Adriamycin (ADR) (doxorubicin; Adria Laboratories, Columbus, OH), and cisplatin (DDP) (M-VAC regimen), significant tumor regression occurred in 72% f 8% of 121 with transitional cell carcinoma (TCC) evaluable for response. Complete remission (CR) was achieved in 36% +-9% of patients, of whom 11% required the addition of surgical resection of residual disease. Although 68% of CR patients have relapsed, CR median s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
224
0
11

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 638 publications
(241 citation statements)
references
References 8 publications
3
224
0
11
Order By: Relevance
“…The median survival time for combination regimens (e.g. methotrexate þ vinblastine, or doxorubicin þ cisplatin) is approximately 8 months (Sternberg et al, 1989). It is known that pretreatment prognostic features have an impact on individual patient outcome, thus the variation in reported survival in patients treated with chemotherapy may be biased by these features (Bajorin et al, 1999;Calabro and Sternberg, 2002).…”
mentioning
confidence: 99%
“…The median survival time for combination regimens (e.g. methotrexate þ vinblastine, or doxorubicin þ cisplatin) is approximately 8 months (Sternberg et al, 1989). It is known that pretreatment prognostic features have an impact on individual patient outcome, thus the variation in reported survival in patients treated with chemotherapy may be biased by these features (Bajorin et al, 1999;Calabro and Sternberg, 2002).…”
mentioning
confidence: 99%
“…4,5 However, this regimen has substantial side effects that can be life threatening: Nausea/emesis, neutropenia, neutropenic fever, mucositis, and renal insufficiency have been reported in a significant proportion of patients, with some toxic deaths reported. 3,4,6 In a recently published trial, a reduced incidence of hematologic and nonhematologic toxicities was reported with the gemcitabine-cisplatin combination compared with M-VAC, although only patients with a good PS and normal renal function were included. 18 New combination regimens have been tested in Phase II studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few patients are long-term survivors, 6 and the toxicities are significant: Grade 3-4 nausea and emesis, 12%; Grade 3-4 neutropenia, 24 -58% (with febrile neutropenia in 10 -25% of patients); severe mucositis, 13-17%; renal failure, 7%; and toxic deaths, 3%. 3,4 New agents, including gemcitabine, [7][8][9][10] paclitaxel, 11 and docetaxel, 12 have shown activity in patients with bladder and urinary tract transitional cell carcinomas. In Phase II trials, gemcitabine has been combined successfully with cisplatin, [13][14][15] paclitaxel, 16 and paclitaxel plus carboplatin, 17 producing interesting response rates and median survivals.…”
mentioning
confidence: 99%
“…Anti-tumour activity has been demonstrated with several single agents, but does not prolong survival. Cisplatin-based combination chemotherapy leads to response rates between 35% and 70% and is more effective than cisplatin alone (Sternberg et al, 1989;Harker et al, 1985;Foss'a et al, 1982;Loehrer et al, 1992). Typically, the response rates from single institution studies are superior to those from multicentre trials.…”
mentioning
confidence: 99%
“…Typically, the response rates from single institution studies are superior to those from multicentre trials. Prolonged survival has been reported in patients who achieve complete response (CR) (Logothetis et al, 1985;Stoter et al, 1987;Sternberg et al, 1989). Systemic cisplatin-based combination chemotherapy can be toxic, particularly in elderly patients.…”
mentioning
confidence: 99%